76. Comparison between synthetic and digital mammography in different breast tomosynthesis systems. (December 2018) - Bertolini, M.; Baldelli, P.; Contillo, A.; Gala, G. Della; Golinelli, P.; Pagan, L.; Rivetti, S.; Nitrosi, A.; Taibi, A.
Abstract : Purpose: Purpose of this work is to compare image quality of Synthetic Mammography (SM) and Full Field Digital Mammography (FFDM) in four different Digital Breast Tomosynthesis (DBT) systems by using a semi-anthropomorphic phantom. Methods: Four DBT systems (FujiFilm, GE, Hologic, IMS) were characterized by means of the semi-anthropomorphic CIRS-BR3D phantom. The phantom contains clusters of microcalcifications, fibers and masses embedded in a breast equivalent tissue having a heterogeneous background. For each DBT system two images (DBT and FFDM) were acquired applying clinical setup conditions. FFDM acquisitions were repeated in manual mode for each system with a fixed exposure ratio between DBT and FFDM. Comparative analyses were carried out on the contrasts and sizes of micro calcifications, on the contrasts and shapes of masses, and on the noise power spectrum of the background. The FFDM image acquired in clinical setup conditions was considered the gold standard of the metric. Results: Considering the micro calcifications, contrasts were generally preserved by SM with respect to FFDM, while the sizes of the smaller details slightly increased, probably due to the blurring caused by the filtration stages of the tomographic reconstruction. Regarding the masses, no globally significant differences were noticeable in the contrasts, and the shapes were generally well preserved as well. Finally, concerning the noise power spectra, significant variations only appeared in the high frequency regime, in accordance with the above-mentioned blurring. Conclusions: This preliminary analysis confirms for all systems the criticality of the synthetic image in terms of spatial resolution and noise but does not highlight significant differences in the detection capability of the details of interest. Further investigations will be made considering the DBT+SM combination compared to DBT+FFDM, as well as by extending the present analysis to other mammographic phantoms.